Direct Correlation of Surface Tension and Surface Composition of Ionic Liquid Mixtures—A Combined Vacuum Pendant Drop and Angle-Resolved X-ray Photoelectron Spectroscopy Study - Paap, Ulrike; Seidl, Vera; Meyer, Karsten; Maier, Florian; Steinrück, Hans-Peter (Molecules, 2022)
We investigated the surface tension and surface composition of various mixtures of the two ionic liquids (ILs) 1-methyl-3-octyl-imidazolium hexafluorophosphate [C8C1Im][PF6] and 1,3-bis(polyethylene glycol)imidazolium iodide [(mPEG2)2Im]I in the temperature range from 230 to 370 K under ultraclean vacuum conditions. The surface tension was measured using a newly developed apparatus, and the surface composition was determined by angle-resolved X-ray photoelectron spectroscopy (ARXPS). In the pure ILs, the alkyl chains of [C8C1Im][PF6] and the PEG chains of [(mPEG2)2Im]I are enriched at the IL/vacuum interface. In the mixtures, a strong selective surface enrichment of the alkyl chains occurs, which is most pronounced at low [C8C1Im][PF6] contents. For the surface tension, strong deviations from an ideal mixing behaviour take place. By applying a simple approach based on the surface composition of the mixtures as deduced from ARXPS, we are able to predict and reproduce the experimentally measured temperature-dependent surface tension values with astonishingly high accuracy.
CRIS-Team Scopus Importer:2022-12-23
Keywords: angle-resolved X-ray photoelectron spectroscopy (ARXPS); ionic liquids; pendant drop (PD); surface composition; surface tension; ultra-high vacuum (UHV)